The Bonus Army an American epic - Dickson, Paul; Allen, Thomas B. (Walker, 2004)
In the Depression summer of 1932, some 45,000 veterans of World War I descended on Washington to demand the bonus promised them eight years earlier for their wartime service. They lived in shantytowns, white and black together, protested and rallied for their cause. Roy Wilkins saw the model for racial integration here; J. Edgar Hoover built his reputation against the radicals. President Hoover, Army Chief of Staff Douglas MacArthur, and others feared the protesters would turn violent after the Senate defeated the "bonus bill" that the House had passed. On July 28, tanks rolled as troops evicted the marchers. Newspapers and newsreels showed graphic images of American soldiers driving out their former comrades in arms. Democratic candidate Franklin Roosevelt said to an adviser, "This will elect me," though bonus armies would plague him as well. The march inspired Congress to pass the G.I. Bill of Rights in 1944.--From publisher description.
Includes bibliographical references and index
Keywords: Bonus Expeditionary Forces; Geschichte 1900-2000; Geschichte; Betalingen; Eerste Wereldoorlog; Protestmarsen; Veteranen; Weltkrieg (1914-1918); Wirtschaft; World War, 1914-1918 -- Veterans -- Washington (D.C.); Protest movements -- Washington (D.C.) -- History -- 20th century; Veterans -- United States -- Political activity -- History -- 20th century; Veterans -- United States -- Economic conditions -- 20th century; USA; Washington (D.C.) -- History -- 20th century